Migration Drives the Replacement of Xanthomonas perforans Races in the Absence of Widely Deployed Resistance - Bernal, Eduardo; Rotondo, Francesca; Roman-Reyna, Veronica; Klass, Taylor; Timilsina, Sujan; Minsavage, Gerald V.; Iruegas-Bocardo, Fernanda; Goss, Erica M.; Jones, Jeffrey B.; Jacobs, Jonathan M.; Miller, Sally A.; Francis, David M. (Frontiers in Microbiology, 2022)
Changes in Xanthomonas race and species composition causing bacterial spot of tomato have occurred throughout the world and are often associated with epidemics. Knowledge of bacterial population structure is key for resistance discovery and deployment. We surveyed Xanthomonas spp. composition from processing tomato fields in the Midwestern United States over a four-year period between 2017 and 2020, compared these to strains collected previously, and found that X. perforans is currently the most prevalent species. We characterized 564 X. perforans isolates for sequence variation in avrXv3 to distinguish between race T3 and T4 and validated race designation using hypersensitive response (HR) assays for 106 isolates. Race T4 accounted for over 95% of X. perforans isolates collected in the Midwest between 2017 and 2020. Whole genome sequencing, Average Nucleotide Identity (ANI) analysis, core genome alignment and single nucleotide polymorphism (SNP) detection relative to a reference strain, and phylogenomic analysis suggest that the majority of Midwestern X. perforans strains collected between 2017 and 2020 were nearly identical, with greater than 99.99% ANI to X. perforans isolates collected from Collier County, Florida in 2012. These isolates shared a common SNP variant resulting an a premature stop codon in avrXv3. One sequenced isolate was identified with a deletion of avrXv3 and shared 99.99% ANI with a strain collected in Collier Co., Florida in 2006. A population shift to X. perforans T4 occurred in the absence of widely deployed resistance, with only 7% of tomato varieties tested having the resistant allele at the Xv3/Rx-4 locus. The persistence of nearly identical strains over multiple years suggests that migration led to the establishment of an endemic population. Our findings validate a genomics-based framework to track shifts in X. perforans populations due to migration, mutation, drift, or selection based on comparisons to 146 genomes.